(untitled) (Bangladesh Journal of Neuroscience, 2026)
Stroke is one of the leading causes of death and the number one cause of long-term disability in the Bangladesh. Carotid stenosis is an important cause of ischemic strokes, accounting for 20 to 25%. Both symptomatic and asymptomatic carotid stenosis, carotid endarterectomy are established as a standard care of treatment. Symptomatic patients with carotid stenosis > 50% and asymptomatic patients with carotid stenosis > 70% are candidates for endarterectomy. Recently, carotid artery stenting has emerged as an alternative treatment for carotid stenosis. Several studies have been published comparing endarterectomy with carotid artery stenting. In this article, the authors discuss carotid artery stenting technique, the results from the most recent trials, comparison with endarterectomy and future directions.